2022
DOI: 10.1002/asi.24656
|View full text |Cite
|
Sign up to set email alerts
|

At the crossroads of logics: Automating newswork with artificial intelligence(Re)defining journalistic logics from the perspective of technologists

Abstract: As artificial intelligence (AI) technologies become more ubiquitous for streamlining and optimizing work, they are entering fields representing organizational logics at odds with the efficiency logic of automation. One such field is journalism, an industry defined by a logic enacted through professional norms, practices, and values. This paper examines the experience of technologists developing and employing natural language generation (NLG) in news organizations, looking at how they situate themselves and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…This encompasses a comprehensive repertoire of techniques, including the adept utilization of direct quotations, skillful paraphrasing, and the diligent citation of references (Scherr et al, 2017;Schmidt & Lawrence, 2020). These practices, integral to the foundational fabric of journalistic pedagogy, wield a dual purpose: they confer an enhanced aura of credibility upon the narrative composition and, concurrently, engender a palpable sense of trust within the readership (Sehat, 2022;Sirén-Heikel et al, 2023). The essential crux underpinning this instructional emphasis is the recognition that the strategic deployment of these attribution techniques significantly bolsters the veracity and authenticity of the journalistic discourse.…”
Section: Discussionmentioning
confidence: 99%
“…This encompasses a comprehensive repertoire of techniques, including the adept utilization of direct quotations, skillful paraphrasing, and the diligent citation of references (Scherr et al, 2017;Schmidt & Lawrence, 2020). These practices, integral to the foundational fabric of journalistic pedagogy, wield a dual purpose: they confer an enhanced aura of credibility upon the narrative composition and, concurrently, engender a palpable sense of trust within the readership (Sehat, 2022;Sirén-Heikel et al, 2023). The essential crux underpinning this instructional emphasis is the recognition that the strategic deployment of these attribution techniques significantly bolsters the veracity and authenticity of the journalistic discourse.…”
Section: Discussionmentioning
confidence: 99%
“…In "At the crossroads of logics: Automating newswork with AI (Re)defining journalistic logics from the perspective of technologists," Sirén-Heikel et al (2022) show how the logic of AI systems may diverge and even mitigate journalistic logics and institutionalized norms, practices, and values in journalism. Building on interviews with firms that provide AI solutions for newsrooms, the article represents the perspective of the technologists on the unique role that AI tools (i.e., natural language processing) could play in transforming and automating tasks in journalism, an industry long mediated by information technology.…”
Section: Articles In This Special Issuementioning
confidence: 99%
“…Beckett and Yaseen (2023) have found that innovation/digital teams, dedicated cross‐functional teams, tech/IT departments, or data teams oversee the development of AI strategies in their news organizations. These are specialized units (Cools, Van Gorp, and Opgenhaffen 2022; Kosterich and Royal 2024; Sirén‐Heikel, Kjellman, and Lindén 2023), which many local news organizations will not be able to implement. Nevertheless, local news organizations should at least appoint a specialist to monitor AI developments internally and externally and “keep a conversation going within […] [the] organization about AI” (Beckett & Yaseen, 2023, p. 72).…”
Section: Introductionmentioning
confidence: 99%